Biliary peritonitis due to permeation of gallbladder distention secondary to compression of the common bile duct by an aortic aneurysm - Valls, Alberto; Morelli, Raúl; Fontán, Walter; Liard, W (Cirugía del Uruguay, 1972)
A case of peritonitis due to permeation of the gall bladder became partially necrotic by reason of an obstruction of the common bile duct which was compressed and laminated due to the expansive growth of an aneurism of the abdominal aorta.